The secret : what great leaders know and do. - Blanchard, Kenneth Harry, 1939-; Miller, Mark, 1959- (San Francisco : Berrett-Koehler, 2009)
At one time or another, everyone in a position of authority-whether in a multi-national corporation or a local volunteer group-wonders what the key to great leadership is. And who better to answer that question than the team of Ken Blanchard, whose books on leadership have sold over 20 million copies, and Mark Miller, who worked his way up from line worker to vice president of one of the largest fast-food chains in the country. In The Secret, Blanchard and Miller use the uniquely accessible "business fable" format that Blanchard pioneered to get at the heart of what makes a leader truly able to inspire and motivate people. Debbie Brewster, recently promoted and struggling, finds herself about to lose her job due to poor performance. In an attempt to save her career, she enrolls in a new mentoring program offered by her company. Much to her surprise, Debbie finds her mentor is none other than Jeff Brown, the president of the company. Debbie decides that she is going to ask her new mentor the one question she feels she desperately needs answered: "What is the secret of great leaders?" Jeff's immediate answer-that great leaders serve their followers-completely flummoxes Debbie. Over the next 18 months, Jeff helps Debbie discover and explore five fundamental ways that leaders lead through service. The Secret puts what Blanchard and Miller have learned about leadership in a form that anyone can easily understand, embrace, and pursue. It is a book that will benefit not only those who read it, but also the organizations they work in and the people who look to them for guidance.
Keywords: Leidinggeven